Problem-Based Learning: A Didactic Strategy in the Teaching of System Simulation - Cevallos-Torres, Lorenzo; Botto-Tobar, Miguel (Studies in Computational Intelligence, 2019)
This book describes and outlines the theoretical foundations of system simulation in teaching, and as a practical contribution to teaching-and-learning models. It presents various methodologies used in teaching, the goal being to solve real-life problems by creating simulation models and probability distributions that allow correlations to be drawn between a real model and a simulated model. Moreover, the book demonstrates the role of simulation in decision-making processes connected to teaching and learning.